The Big Five default brain: functional evidence - Sampaio, Adriana (2014)
Recent neuroimaging studies have provided evidence that different dimensions of human personality may be associated with specific structural neuroanatomic correlates. Identifying brain correlates of a situation-independent personality structure would require evidence of a stable default mode of brain functioning. In this study, we investigated the correlates of the Big Five personality dimensions (Extraversion, Neuroticism, Openness/Intellect, Agreeableness, and Conscientiousness) and the default mode network (DMN). Forty-nine healthy adults completed the NEO-Five Factor. The results showed that the Extraversion (E) and Agreeableness (A) were positively correlated with activity in the midline core of the DMN, whereas Neuroticism (N), Openness (O), and Conscientiousness (C) were correlated with the parietal cortex system. Activity of the anterior cingulate cortex was positively associated with A and negatively with C. Regions of the parietal lobe were differentially associated with each personality dimension. The present study not only confirms previous functional correlates regarding the Big Five personality dimensions, but it also expands our knowledge showing the association between different personality dimensions and specific patterns of brain activation at rest.